PERLINDUNGAN HUKUM TERHADAP KONSUMEN JASA PARKIR DALAM HAL TERJADINYA KEHILANGAN TERHADAP KENDARAANNYA - Ismayani, Ni Nyoman; Westra, I Ketut; Sri Indrawati, Anak Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 12, November 2013, 2013)
Consumer protection laws against parking services in the event of loss of the vehicle. The need for parking services are very important to the company established parking area of Denpasar. Practicing of standard clause to redress loss motor vehicle contrary to law customer protection laws. The purpose of this paper, to assess the regional regulations compensates lost motor vehicle. The method used in this paper with the empirical method juridical approach the problem from the provisions of laws - laws. In order to redress loss vehicle, the consumer must meet the requirements set.
Keywords: Consumer, Parking, Compensation, Loss